Bioequivalence studies in Europe before and after 2010. (March 2015) - Daousani, Chrysa; Karalis, Vangelis
Abstract Regulatory guidelines are necessary to standardize the evaluation procedure in bioequivalence. Revisions in the guidelines occur in order to resolve any previously unclear issues and to address new needs. In this paper, the authors discuss the major regulatory requirements for bioequivalence assessment before and after the EMA guidelines of 2010 and unveil their differences. The authors compiled this review following the critical exploration of literature articles and regulatory guidance documents. This was achieved through searching MEDLINE, Scopus, and the official EMA site. The authors found, in the post-2010 era, that the major differences in the regulatory framework refer to: the choice of clinical designs, the assessment of highly variable drugs, biowaivers, the pharmacokinetics parameters used, and the explicit definition for the use of metabolite data, enantiomers, and endogenous substances. Also, product-specific guidelines have started to be issued, while recommendations are now provided for some special formulations like orodispersible tablets. Other issues were elucidated like studies in the fasting or fed state and the dissolution assessment. The EMA regulatory framework on bioequivalence changed significantly in the post-2010 era. Many issues are now defined more explicitly, while others are newly introduced. However, some issues remain unresolved.